Comparison of the toxicogenetic potential of sewage sludges from different treatment processes focusing agricultural use - Caritá, Renata [UNESP]; Mazzeo, Dânia Elisa Christofoletti [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Springer Nature, 2019)
A problem that has been dragging in recent decades is the final disposal of the waste produced in the wastewater treatment process. In addition to its high amount of organic matter and nutrients, this waste, known as sewage sludge (SS), may also contain toxic compounds that, when in the environment, can cause deleterious effects to organisms and lead to severe and irreversible consequences to human health. In order to understand the potential of inducing cellular and chromosomal instabilities, the species Allium cepa was employed to assess the presence of toxic agents in SS samples. Seeds of A. cepa were exposed to several dilutions of aqueous extract of SSs from 5 wastewater treatment plants (WWTPs), whose characteristics of treated sewage and the technologies employed differ among them. The results obtained showed that all the studied SSs induced significant genotoxic and mutagenic alterations, even in smaller dilutions tested. With these results, it was also possible to observe that SSs from WWTPs that present system of activated sludge and receive sewage of industrial origin induced a greater number of toxicogenetic alterations in the test organism. The high frequencies of chromosomal and nuclear aberrations observed, induced by contaminants present in the SS, represent worrying results because it proves a direct action of this agent on the genetic material of the exposed organism. Therefore, the agronomic application of SS in agriculture requires additional and more effective technologies in order to promote its complete decontamination and its safe disposal in the environment.
Keywords: Allium cepa; Chromosomal aberrations; Genotoxicity; Micronuclei; Waste management; Wastewater treatment